FABRICATION, OPTIMIZATION AND IN VITRO CYTOTOXICITY EVALUATION OF DASATINIB MONOHYDRATE-LOADED NANOPARTICLES - SAROHA, AJAY; VERMA, RAVINDER; MITTAL, VINEET; KAUSHIK, DEEPAK (International Journal of Applied Pharmaceutics, 2024)
Objective: The present research aimed to formulate, optimize and evaluate dasatinib monohydrate-loaded nanoparticles using the ionic gelation method as a potential anticancer drug delivery system for enhancing its dissolution rate. Methods: Box-Behnken design was implemented to study the effects of selected parameters chitosan concentration (X1), Sodium Tripolyphosphate (NaTPP) concentration (X2), and NaTPP volume (X3) on the drug release from developed nanoparticles. Moreover, optimized formulation was evaluated for various parameters, including X-ray diffraction, differential scanning calorimetry, fourier transform infra-red, in vitro drug release and drug kinetics. Then, in vitro cytotoxicity was executed via MTT assay method on leukemia cell lines (RPMI 8226). Results: The results showed optimal conditions for maximum encapsulation efficiency and minimum particle size were a low chitosan concentration, a medium NaTPP concentration, and a high NaTPP volume. The optimized batch (NP-7) demonstrated promising results with an encapsulation efficiency of 83.12±0.17%, particle size of 96.8 nm, and an in vitro cumulative drug release of 91.37±0.49% after 24 h. The cytotoxicity of dasatinib monohydrate was higher when administered in polymeric nanoparticles (NP-7) as compared to its pure form. Conclusion: From this research, it can be concluded that the drug release was enhanced when dasatinib monohydrate was loaded into chitosan nanoparticles.